Quality of Maternal Height and Weight Data from the Revised Birth Certificate and Pregnancy Risk Assessment Monitoring System. Issue 1 (January 2019) - Deputy, Nicholas P.; Sharma, Andrea J.; Bombard, Jennifer M.; Lash, Timothy L.; Schieve, Laura A.; Ramakrishnan, Usha; Stein, Aryeh D.; Nyland-Funke, Michael; Mullachery, Pricila; Lee, Erica
Abstract : Background: The 2003 revision of the US Standard Certificate of Live Birth (birth certificate) and Pregnancy Risk Assessment Monitoring System (PRAMS) are important for maternal weight research and surveillance. We examined quality of prepregnancy body mass index (BMI), gestational weight gain, and component variables from these sources. Methods: Data are from a PRAMS data quality improvement study among a subset of New York City and Vermont respondents in 2009. We calculated mean differences comparing prepregnancy BMI data from the birth certificate and PRAMS (n = 734), and gestational weight gain data from the birth certificate (n = 678) to the medical record, considered the gold standard. We compared BMI categories (underweight, normal weight, overweight, obese) and gestational weight gain categories (below, within, above recommendations), classified by different sources, using percent agreement and the simple κ statistic. Results: For most maternal weight variables, mean differences between the birth certificate and PRAMS compared with the medical record were less than 1 kg. Compared with the medical record, the birth certificate classified similar proportions into prepregnancy BMI categories (agreement = 89%, κ = 0.83); PRAMS slightly underestimated overweight and obesity (agreement = 84%, κ = 0.73). Compared with the medical record, the birth certificate overestimated gestational weight gain below recommendations and underestimated weight gain within recommendations (agreement = 81%, κ = 0.69). Agreement varied by maternal and pregnancy-related characteristics. Conclusions: Classification of prepregnancy BMI and gestational weight gain from the birth certificate or PRAMS was mostly similar to the medical record but varied by maternal and pregnancy-related characteristics. Efforts to understand how misclassification influences epidemiologic associations are needed. Abstract : Supplemental Digital Content is available in the text.